BENEFITS OF USING REFLEXOTHERAPY FOR TYPES OF HEADACHES (International journal of medical sciences, 2025)
This article discusses the types of headaches, their frequency, causes, and methods of treatment. Nowadays, the symptom that bothers many people is a headache. Headaches have become a background of the disease, and when we have a headache, we are wary of many medications. The medications we take for a simple headache cause serious harm to our body organs. The medicine we take, first of all, affects the gastrointestinal tract, the liver, and even the most harmless drug, of course, causes significant damage to the kidneys. However, this problem can be eliminated without medication, by affecting the reflexes and using light massage techniques. More than 150 different types of headaches are divided into three main categories - primary headaches, secondary headaches, and cranial neuralgia.